(untitled) (Heritage, 2025)
Exposing some of Darren Kelsey’s and John Langer’s basic assumptions, the authors point out the similarities of their concepts. While relying on discourse analysis and Carl Gustav Jung’s theory on collective unsconsious, Darren Kelsey points to narratives from distant past, while John Langer observes the persistent presence of so - called ’other news’ in media space. Darren Kelsey draws conclusions on the British, and John Langer on Australian media content. Although the first author insists on intangible and latent representations that invoke strong emotional responses in news consumers, the other observes several reoccurring patterns that draw the attention of viewers and listeners from important existential questions to celebrities, tragedies, gossip and weather forecasting. Both authors, although in different manners prove that media content can be reduced to several patterns that evoke strong emotional responses in viewers. Whether they trigger archetypal images, or identification with celebrities, these stories enable the status quo to be maintained in the background of ‘objective reporting.’ They trigger aggression towards internal/external enemy, spread or soothe the anxiety of citizens. Media, archetype, stereotype and contemporary media narrative meet at the same point. In ‘other’ or main news, heroes, tricksters, shadows, wars between good and evil, function as general places that maintain the flow of news, enable the mobilization of population to initiate conflicts, or divert the attention from important local and global news.